A cryogenic solid-state reaction at the interface between Ti and the Bi2Se3 topological insulator. Issue 33 (20th July 2020) - Ferfolja, Katja; Fanetti, Mattia; Gardonio, Sandra; Panighel, Mirco; Píš, Igor; Nappini, Silvia; Valant, Matjaz
Abstract : Titanium deposited on the Bi2 Se3 surface reacts (even at 130 K) and forms new phases. Abstract : Understanding the chemical processes at the interface between a metal and topological insulator (TI) is important when it comes to designing devices that exploit the peculiar topological surface states or studying the properties of TI heterostructures. In this paper we show that the interface between Ti and Bi2 Se3 is unstable at RT and results in the formation of interfacial phases of titanium selenides and metallic Bi. The reaction has shown significant kinetics already at cryogenic temperatures, which is very surprising for a solid-state redox reaction. This can be explained with the possibility of electrons in the topological surface states playing a role in enhancing the Bi2 Se3 surface reactivity due to the electron-bath effect. For the Ti coverage above 40 nm, the interfacial processes cause compressive stress that triggers the morphological change (buckling) of the deposited film. The observed interface reaction, with all of its consequences, has to be considered not only in the design of devices, where the Ti adhesion layer is often used for contacts, but also for possible engineering of 2D TI heterostructures.